The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1017/wsc.2018.75
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crop Termination Treatment Impacts Weed Suppression Potential

Abstract: Weed management in tobacco (Nicotiana tabacumL.) is accomplished primarily with soil-residual herbicides, cultivation, and hand removal. Management practices that reduce weed emergence, like reduced tillage and cover crop mulches, may improve weed management efficacy. Depending on cover-cropping goals, growers face trade-offs in species selection and management priorities—producing weed-suppressive mulches may lead to transplanting difficulties and soil-residual herbicide interception. Managing more complex co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Agronomic practices can affect the weed flora and species composition of the weed community and soil seed bank in arable fields [7]. Crop rotation [8,9], fertilization [10][11][12][13], tillage [14][15][16], and crop residue retention [17][18][19] are effective measures to control weeds. No-till has been widely accepted in recent decades for many environmental benefits, such as reducing run-off, improving nutrient cycling, reducing soil degradation, decreasing water and soil pollution, and enhancing the activities of soil biota [20].…”
Section: Introductionmentioning
confidence: 99%
“…Agronomic practices can affect the weed flora and species composition of the weed community and soil seed bank in arable fields [7]. Crop rotation [8,9], fertilization [10][11][12][13], tillage [14][15][16], and crop residue retention [17][18][19] are effective measures to control weeds. No-till has been widely accepted in recent decades for many environmental benefits, such as reducing run-off, improving nutrient cycling, reducing soil degradation, decreasing water and soil pollution, and enhancing the activities of soil biota [20].…”
Section: Introductionmentioning
confidence: 99%
“…Greater amounts of precipitation reduce carryover potential (Tharp and Kells 2000) and resulted in less herbicide retention on surface residues (Ghadiri et al 1984). Moreover, sulfentrazone plus carfentrazone applied over heavy cover crop residues resulted in good weed control when rainfall occurred soon after application, suggesting retention on residues was not occurring (Haramoto and Pearce 2019). In 2016, 346 and 477 mm of precipitation fell between herbicide applications (the POST clomazone and the PREs, respectively) and cover crop planting, whereas 474 and 690 mm of precipitation fell in 2017 during these intervals.…”
Section: Weather Conditionsmentioning
confidence: 99%
“…Though in-season cultivation is more difficult with these management practices, the combination of cover crops with strip tillage may contribute to WM by creating surface mulches that reduce weed emergence and suppress growth (Brainard et al 2013). Our previous research with strip-tilled tobacco has shown that more cover crop residue led to lower weed density but that a soil-residual herbicide was still necessary for adequate weed control (Haramoto and Pearce 2019). Although soil-residual herbicides do not provide adequate full-season control, they may still interfere with successful establishment and growth of subsequently planted cover crops (Cornelius and Bradley 2017;Palhano et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies show that with the use of traditional machines, the entire minimization often comes down to replacing plowing with rootless processing methods, unjustified simplification of technology, or replacing mechanical operations with herbicides. In most cases, the quality of processing remains unsatisfactory and gives a low economic effect (Demir & Gözübüyük, 2019;Haramoto & Pearce, 2019;Obade, 2019). Obviously, a dispute about the advantages and disadvantages of dumping and dumping tillage methods, especially proposals to universalize the use of each of them, which has been going on for the last decades, can only be resolved on the basis of new conceptual approaches to the technology of growing crops using a new-generation agricultural equipment.…”
Section: Introductionmentioning
confidence: 99%